2020
DOI: 10.1038/s41598-020-73041-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of metabolites and metabolic pathways in three maize (Zea mays L.) varieties from the same origin using GC–MS

Abstract: Metabolites of the Jinyu 88, Huanong 18, and Demeiya 9 maize varieties from the same origin were isolated and identified by GC–MS, and the specific metabolites and metabolic mechanisms of these three varieties of maize were preliminarily analysed and discussed. The metabolites were extracted with 80% methanol and derived with N,O-bis(trimethylsilyl)trifluoroacetamide. A total of 59 metabolites were identified. The specific metabolites of these three varieties of maize were identified. Four possible unknown-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Xylose is a crucial part of the hemicellulose and does not exist in its free form. Agricultural waste products are considered one of the major sources of xylose ( Zhang, Yu, & Yu, 2020 ). From the aforementioned, it was found that except for W, all four polysaccharides contained significant amounts of xylose.…”
Section: Resultsmentioning
confidence: 99%
“…Xylose is a crucial part of the hemicellulose and does not exist in its free form. Agricultural waste products are considered one of the major sources of xylose ( Zhang, Yu, & Yu, 2020 ). From the aforementioned, it was found that except for W, all four polysaccharides contained significant amounts of xylose.…”
Section: Resultsmentioning
confidence: 99%
“…Plants synthesize hundreds of thousands of metabolites, and different species and genera produce different types of primary and secondary metabolites (Allwood et al, 2008). Both primary and secondary metabolites play important roles in plant stress resistance (Zaynab et al, 2018;Zhang et al, 2020). In this study, only the Frontiers in Ecology Evolution 08 frontiersin.org methanol-water phase was derivatized and analyzed by GC-MS, as a result mainly primary metabolites were identified in this study.…”
Section: Stability Of the Major Metabolite Composition Of Plant Speciesmentioning
confidence: 99%
“…The chemicals used were qualitative and quantitative with ions, the information obtained was organized, and the specific metabolites of the different Masson pine families were characterized. The metabolites were classified using standard methods, and referencing the associated literature (Zhang et al, 2020). The statistical analyses were performed using the R (version 4.0.0) software (Kanehisa and Goto, 2000;Chong and Xia, 2018).…”
Section: Data Pre-processing and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental cues are naturally occurring-temperature, light intensity, precipitation, and various stressors-or result from agricultural management practices-such as soil organic matter and nutrient levels (Zhu et al, 2007;Hirschi, 2009;Fatima et al, 2016;Vasconcelos et al, 2017;Roberts and Mattoo, 2019). Several studies have demonstrated the influence of genetics (crop varieties) and naturally occurring cues (year, drought, geographic location) on the biochemical composition of maize grain and other maize tissues (Reynolds et al, 2005;Röhlig et al, 2009;Anttonen et al, 2010;Röhlig and Engel, 2010;Frank et al, 2012;Baniasadi et al, 2014;Chen et al, 2016;Venkatesh et al, 2016;Zhang L. et al, 2020;Gaffney et al, 2021;Zhang et al, 2021). But there has been less work on maize grain biochemical composition and environmental cues resulting from agricultural management practices in replicated experiments.…”
Section: Introductionmentioning
confidence: 99%